PENGEMBANGAN DAN VALIDASI KUESIONER UNTUK MENGUKUR PENGETAHUAN PENGGUNAAN ANTIBIOTIK PADA MASYARAKAT KOTA WILAYAH KEPULAUAN BANGKA BELITUNG - Lana Sari; Mirnawati Zalili Sailan (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2023)
Diseases caused by bacteria are treated with antibiotics. Antibiotics can be a threat globally, especially related to high resistance rates. Research has found that 40-62% of antibiotics are abused for diseases that do not require antibiotics for treatment. The results of research conducted by WHO from 12 countries, one of which is Indonesia, as many as 53-62% stops using antibiotics if they feel they have recovered. This study aims to develop and validate a questionnaire used to measure knowledge of antibiotic use in the people of Pangkalpinang City, Archipelago Region. The study was conducted in Pangkalpinang City from May to June 2022. This study involved 10 pharmacists as a panel of experts and 30 residents of Pangkalpinang City. The sampling technique was cluster sampling and tested the validity and reliability of the questionnaire. The results of the content validity test obtained the value of the content validity index (I-CVI) of each statement item. The content validity test was carried out in two rounds and the I-CVI value was 0.94 so that it could be concluded that the questionnaire was valid with 42 statement items. After that, it was continued with validity and reliability tests involving 30 people in Pangkalpinang City. The results of this validity test obtained 39 valid statements, and for the reliability test, the KR 20 value was 0.8. Questionnaires can be used to measure the level of knowledge of the use of antibiotics in cities and communities on the island.